(untitled) (Mustansiria Dental Journal, 2018)
The success of metal-ceramic restorations is influenced by the compatibility between base metal alloys and porcelains. Although porcelain manufacturers recommend their own metal systems as the most compatible for fabricating metalceramic prostheses, a number of alloys have been used. The purpose of this study was to evaluate the bond strength of CoCr alloy (Wironbond C) and NiCr alloy (Wiron 99) using shear forces at the metal-ceramic interface. A stainless steel cylindrical matrix was used for preparation of the metal dies, application of ceramic and to perform the shear tests. Ten metal dies of each alloy were made for each alloy, and the metallic portion was obtained with the lost wax casting technique with standardized waxing of 6.5mm of height and of 6mm of diameter. The ceramic was applied according to the manufacturer’s recommendations with the aid of a Teflon matrix that allowed its dimension to be standardized in the same size as the metallic portion, and shear tests were performed in a universal testing machine at a cross-head speed of 0.5mm/min. The mean shear bond strength values were 53.06MPa for Wirobond C alloy, with standard deviation of 10.67, and 45.38MPa for Wiron 99, with standard deviation of 9.01. No statistically significant difference was observed between the shear strength of the two metal-ceramic alloys.